Minimally invasive sampling to identify leprosy patients with a high bacterial burden in the Union of the Comoros. - Sofie Marijke Braet; Anouk van Hooij; Epco Hasker; Erik Fransen; Abdou Wirdane; Abdallah Baco; Saverio Grillone; Nimer Ortuno-Gutierrez; Younoussa Assoumani; Aboubacar Mzembaba; Paul Corstjens; Leen Rigouts; et al. (Public Library of Science (PLoS), 2021)
The World Health Organization (WHO) endorsed diagnosis of leprosy (also known as Hansen's disease) entirely based on clinical cardinal signs, without microbiological confirmation, which may lead to late or misdiagnosis. The use of slit skin smears is variable, but lacks sensitivity. In 2017-2018 during the ComLep study, on the island of Anjouan (Union of the Comoros; High priority country according to WHO, 310 patients were diagnosed with leprosy (paucibacillary = 159; multibacillary = 151), of whom 263 were sampled for a skin biopsy and fingerstick blood, and 260 for a minimally-invasive nasal swab. In 74.5% of all skin biopsies and in 15.4% of all nasal swabs, M. leprae DNA was detected. In 63.1% of fingerstick blood samples, M. leprae specific antibodies were detected with the quantitative αPGL-I test. Results show a strong correlation of αPGL-I IgM levels in fingerstick blood and RLEP-qPCR positivity of nasal swabs, with the M. leprae bacterial load measured by RLEP-qPCR of skin biopsies. Patients with a high bacterial load (≥50,000 bacilli in a skin biopsy) can be identified with combination of counting lesions and the αPGL-I test. To our knowledge, this is the first study that compared αPGL-I IgM levels in fingerstick blood with the bacterial load determined by RLEP-qPCR in skin biopsies of leprosy patients. The demonstrated potential of minimally invasive sampling such as fingerstick blood samples to identify high bacterial load persons likely to be accountable for the ongoing transmission, merits further evaluation in follow-up studies.